Reduced Interhemispheric Coherence in Cerebellar Kainic Acid-Induced Lateralized Dystonia - Georgescu Margarint, Elena Laura; Georgescu, Ioana Antoaneta; Zahiu, Carmen Denise Mihaela; Tirlea, Stefan-Alexandru; Şteopoaie, Alexandru Rǎzvan; Zǎgrean, Leon; Popa, Daniela; Zǎgrean, Ana-Maria (Frontiers in Neurology, 2020)
The execution of voluntary muscular activity is controlled by the primary motor cortex, together with the cerebellum and basal ganglia. The synchronization of neural activity in the intracortical network is crucial for the regulation of movements. In certain motor diseases, such as dystonia, this synchrony can be altered in any node of the cerebello-cortical network. Questions remain about how the cerebellum influences the motor cortex and interhemispheric communication. This research aims to study the interhemispheric cortical communication between the motor cortices during dystonia, a neurological movement syndrome consisting of sustained or repetitive involuntary muscle contractions. We pharmacologically induced lateralized dystonia to adult male albino mice by administering low doses of kainic acid on the left cerebellar hemisphere. Using electrocorticography and electromyography, we investigated the power spectral densities, cortico-muscular, and interhemispheric coherence between the right and left motor cortices, before and during dystonia, for five consecutive days. Mice displayed lateralized abnormal motor signs, a reduced general locomotor activity, and a high score of dystonia. The results showed a progressive interhemispheric coherence decrease in low-frequency bands (delta, theta, beta) during the first three days. The cortico-muscular coherence of the affected side had a significant increase in gamma bands on days 3 and 4. In conclusion, lateralized cerebellar dysfunction during dystonia was associated with a loss of connectivity in the motor cortices, suggesting a possible cortical compensation to the initial disturbances induced by cerebellar left hemisphere kainate activation by blocking the propagation of abnormal oscillations to the healthy hemisphere. However, the cerebellum is part of several overly complex circuits, therefore other mechanisms can still be involved in this phenomenon.